Globalisation, media trust, and populism: A comparative study of the US and Germany. (October 2022) - Yan, Pu; Schroeder, Ralph
Globalisation is an area where supporters and non-supporters of left- and right-wing parties disagree, both for domestic and international policies. Populists see metropolitan elites as 'corrupt' and oppose policies that encourage globalisation in trade, immigration, and multi-culturalism. Media play important roles in providing pro- and anti-globalisation content, both in traditional and digital media. We use a unique combination of large-scale web-tracking and cross-country survey data to study the interactions between populism, media trust, consumption, and globalisation attitudes in the US and Germany. We find country variances for different aspects of globalisation, particularly among the supporters of right-wing populist parties or leaders. Populist anti-elitism and a feeling of powerlessness in relation to influencing the country's politics are two important factors behind the backlash against globalisation. We also find that a higher level of trust in public service media is associated with more supportive attitudes toward globalisation.